De la légitimité des chanteurs zouglou dans l’espace politique ivoirien - Amadou Ouattara ADOU (Altralang Journal, 2021)
ABSTRACT: Political discourse is defined as a discourse on city’s management. Let’s us admit with Charaudeau (2005) that it is produce by three instances: the politicians, the media and the Citizens. He assigns specific functions to each of these instances. For example, the political leaders produce a discourse that announces, justifies or challenges political actions, while other instances produce analysis or comments on the actions or statements of first instance. In any event, these various productions must be placed in a context that justifies their political character. Lezou Koffi and Adou (2019) show that the zouglou, urban music of Côte d’Ivoire born in a context of socio-economic demands, is a place where political discourse is made. To do so, they demonstrate that the zouglou texts carry social ideals and can be included in a communication contract that presents them as political commentary. Following this contribution, we would like to question the mechanisms of the construction of the legitimacy of the zouglou artists as political actors in theirs texts.